Copper homeostasis at the host vibrio interface: lessons from intracellular vibrio transcriptomics. (21st December 2015) - Vanhove, Audrey S.; Rubio, Tristan P.; Nguyen, An N.; Lemire, Astrid; Roche, David; Nicod, Julie; Vergnes, Agnès; Poirier, Aurore C.; Disconzi, Elena; Bachère, Evelyne; Le Roux, Frédérique; Jacq, Annick; et al.
Summary: Recent studies revealed that several vibrio species have evolved the capacity to survive inside host cells. However, it is still often ignored if intracellular stages are required for pathogenicity. Virulence of V ibrio tasmaniensis LGP32, a strain pathogenic for C rassostrea gigas oysters, depends on entry into hemocytes, the oyster immune cells. We investigated here the mechanisms of LGP32 intracellular survival and their consequences on the host–pathogen interaction. Entry and survival inside hemocytes were required for LGP32‐driven cytolysis of hemocytes, both in vivo and in vitro . LGP32 intracellular stages showed a profound boost in metabolic activity and a major transcription of antioxidant and copper detoxification genes, as revealed by RNA sequencing. LGP32 isogenic mutants showed that resistance to oxidative stress and copper efflux are two main functions required for vibrio intracellular stages and cytotoxicity to hemocytes. Copper efflux was also essential for host colonization and virulence in vivo . Altogether, our results identify copper resistance as a major mechanism to resist killing by phagocytes, induce cytolysis of immune cells and colonize oysters. Selection of such resistance traits could arise from vibrio interactions with copper‐rich environmental niches including marine invertebrates, which favour the emergence of pathogenic vibrios resistant to intraphagosomal killing across animal species.